OPTIMALISASI HALAMAN LANDING PAGE UNTUK INDUSTRI FURNITUR: SEBUAH STUDI KASUS MENGGUNAKAN GT METRIX - Broto, Taukhid Wisnu; Ulfia, Yessi Nasia; Arini, Nuskha Ilma (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2024)
The furniture industry faces challenges in marketing its products online, especially due to the limitations of providing customers with a physical product experience. This makes the Landing page a crucial element in digital marketing strategies, which not only needs to be aesthetically appealing but also technically optimized to enhance user engagement and sales conversion. This study aims to identify the factors affecting page load speed and performance of the Landing page, as well as to implement optimization strategies to improve efficiency and user experience. The methods used include literature reviews, direct observation, and technical testing and optimization using the GTMetrix tool. The results show that after technical optimizations, the Landing page performance improved by 8%, page structure increased by 5%, Largest Contentful Paint (LCP) decreased by 0.1 seconds, Total Blocking Time (TBT) reduced by 3 milliseconds, and Cumulative Layout Shift (CLS) decreased by 0.12. In addition, the page performance grade increased from B to A. The conclusion of this study emphasizes the importance of integrating attractive design and high technical performance to achieve an optimal Landing page in the furniture industry, supporting improved user engagement and sales conversion.